IMPLEMENTATION OF SNOWBALL THROWING TECHNIQUE TO IMPROVE READING COMPREHENSION OF GRADE 8 STUDENTS - Lus Firdaus Zakiya (Universitas Islam Sumatera Utara, 2018)
In learning English, reading is one of the most important skills to learn. In the preliminary study, the 8th grade students (grade 8.2) of SMPN 2 Jatirejo Mojokerto had difficulties in understanding reading texts and lacked motivation in participating in learning activities. These problems contradict the 2013 curriculum, where students are expected to be able to understand reading well and be active during learning activities. Therefore, cooperative learning was chosen to be the right strategy in solving these problems because it can provide opportunities for students to work more in groups. In solving problems in the classroom, cooperative learning has several techniques to be applied. One of the teaching techniques of cooperative learning is the Snowball Throwing Technique (hereinafter STT). To improve students' reading comprehension skills and their participation in learning activities, the writer apply STT which allows students to work in groups by discussing, asking questions, answering questions, and having an interesting way of learning in understanding reading texts.